NAVIGATING TEACHERS’ PREPAREDNESS AND PROFESSIONAL DEVELOPMENT: A NARRATIVE INQUIRY IN AN INDONESIAN ISLAMIC BOARDING SCHOOL - Dodi Zain; Irsalina Murtiek (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2026)
This study examines English as a Foreign Language (EFL) teachers’ reflections on teaching preparedness and professional development within the distinctive context of an Islamic Boarding School (IBS) in Indonesia. Employing a narrative inquiry approach, this study was conducted with Aisyah, a female English teacher at an IBS in Banyumas Regency, Central Java. Data were gathered through interviews and subjected to narrative analysis. The findings indicate that teacher preparedness and professional development emerged as dynamic, context-dependent processes shaped by the interaction of teacher agency, reflective practice, experiential learning, and institutional support. The findings further suggest that sustained teacher growth in Islamic boarding schools requires contextually relevant professional development that integrates pedagogical competence with faith-based educational values. This study underscores the need to strengthen alternative pedagogical preparation, mentoring, and context-specific professional development programs to support teachers from diverse educational backgrounds in Islamic boarding schools. They also suggest further comparative and longitudinal research to examine how institutional contexts, reflective practice, and support systems shape teacher preparedness, professional growth, and professional identity over time.